STRENGTHENING STUDENTS’ ACADEMIC COMPETENCE THROUGH EXPERIENCE-BASED LEARNING ACROSS VARIOUS COURSES AT IAI PADANG LAWAS - Nur Royhana Hsb; Jekson Hasibuan; Neni Mika Triana; Hamka (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Higher education is required to integrate theoretical mastery with contextual experience to produce academically and professionally competent graduates. This study aims to analyze the implementation of experience-based learning across several courses at the Institute of Islamic Studies (IAI) Padang Lawas, including Learning Theories and Instructional Methods, the Indonesian Legal System, Listening Skills in Language Learning, Mathematics Learning Methodology, Elementary School Mathematics, Educational Assessment, and Educational Evaluation. A descriptive qualitative approach was employed using observation, interviews, and documentation. The findings reveal that experience-based learning consistently enhances students’ conceptual understanding, analytical ability, and reflective skills across disciplines. These results confirm the relevance of contextual learning approaches in strengthening students’ academic competence in higher education.